PS 18-13 SALT INTAKE BELIEF, KNOWLEDGE AND BEHAVIOR AMONG OLDER RURAL CHINESE ADULTS. (September 2016) - Zhang, Jing; Wu, Tao; Chu, Hongling; Feng, Xiangxian; Shi, Jingpu; Zhang, Ruijuan; Zhang, Yuhong; Zhang, Jianxin; Li, Nicole; Yan, Lijing; Niu, Wenyi; Wu, Yangfeng
Abstract : Objective: Excess sodium consumption is a major cause of high blood pressure and subsequent vascular disease. However, factors driving people's salt intake behavior remains largely unknown. Excess sodium consumption is a major cause of high blood pressure and subsequent vascular disease. However, factors driving people's salt intake behavior remains largely unknown. Design and Method: Study aim is to assess the relationship of salt intake behaviors with knowledge and belief on salt and health among older adults in rural China. A cross-sectional survey was conducted among 4, 693 older participants (male 50 and female 60 years old) randomly selected from 120 rural villages in 5 Northern provinces in China. Healthy salt intake behavior was defined as either not eating pickled foods or not adding pickles/soy sauce/salt when food was not salty enough in past 3 months. Results: There were 81% participants having healthy salt intake behavior. Healthy salt intake behavior was more common among women (p < 0.01) and was positively associated with age (p < 0.01) and poorer health status (p < 0.01), but negatively associated with years in school (p < 0.05). After adjusting for age, gender, years in school, and health status, participants who believed in the harm of high salt intake were more likely to have healthy salt intake behavior, compared with those who did not believe (Odds Ratio = 1.6, p < 0.001). Knowledge of salt intake was not significantly related to healthy salt intake behavior. Conclusions: Our study demonstrated that belief in harm of high salt intake rather than knowledge on salt and health was associated with healthy salt intake behavior, independent of age, sex, years in school and health status. Future population salt reduction program should place more emphasis on establishing health belief rather than only on delivering salt-related knowledge.